Brasilvision as a pedagogy of fantasy and symbolic displacement in Fashion Design education (Revista de Ensino em Artes, Moda e Design, 2026)
This paper analyzes the pedagogical project Brasilvision as a device of applied imagination and symbolic displacement in Fashion Design education. The proposal consisted of randomly assigning Brazilian states to student groups, who were then challenged to translate territorial identity and musical repertoire into performative costume and scenography inspired by an international music festival format. Grounded in Gianni Rodari’s concepts of play and the fantastic binomial, the study understands chance as a structuring force in the creative process, capable of displacing students from aesthetic comfort zones and generating productive tensions between heterogeneous elements. Methodologically, this is an applied, qualitative, and exploratory study based on interpretative analysis of design processes, visual panels, sketchbooks, and the developed costumes and stage models. The results demonstrate that randomness functioned as a pedagogical trigger, transforming initial estrangement into structured aesthetic investigation and resulting in integrated narrative systems between costume and stage space. We conclude that Brasilvision constitutes a pedagogy of imagination in fashion education, articulating play, cultural research, and intersemiotic translation as foundations for critical and inventive learning.
Keywords: fashion education; costume design; imagination; performance art; cultural identity